Building the Bridge From Aquatic Nanotoxicology to Safety by Design Silver Nanoparticles - Corsi, Ilaria; Desimone, Martin Federico; Cazenave, Jimena (Frontiers in Bioengineering and Biotechnology, 2022)
Nanotechnologies have rapidly grown, and they are considered the new industrial revolution. However, the augmented production and wide applications of engineered nanomaterials (ENM) and nanoparticles (NPs) inevitably lead to environmental exposure with consequences on human and environmental health. ENM/Ps effects on humans and the environment are complex and largely depend on the interplay between their peculiar properties such as size, shape, coating, surface charge, degree of agglomeration or aggregation, etc and those of the receiving media/body. This rebounds on ENM/Ps safety and newly developed concepts such as the safety-by-design are gaining importance in the field of sustainable nanotechnologies. This article aims to review the critical characteristics of the ENM/Ps that need to be addressed in the safe by design process to develop ENM/Ps able to reduce/minimize any potential toxicological risks for living beings associated with their exposure. Specifically, we focussed on silver nanoparticles (AgNPs) due to an increasing number of nanoproducts containing AgNPs, as well as an increasing knowledge about this NM and its effects. We review the ecotoxicological effects documented on freshwater and marine species that demonstrated the importance of the relationship between the ENM/Ps design and their biological outcomes in terms of environmental safety.